Effect of lucerne (Medicago sativa) fodder supplementation on nutrientutilization and enteric methane emission in male buffalo calves fed onwheat straw based total mixed ration - MALIK, P K; SINGHAL, K K (The Indian Journal of Animal Sciences, 2011)
Saponin content of lucerne (Medicago sativa) fodder was estimated at 3, viz. I, II and III cuts. Saponin content at II cut (flowering stage) was highest which decreased in the subsequent cut almost to the level of first cut. Male Murrah buffalo calves (6) were initially fed on wheat straw based total mixed ration (TMR–1) consisting R: C as 60:40 and data were recorded thereafter, these animals were shifted on isonitrogenous TMR–2 having 30 % incorporation of lucerne fodder (II cut) as source of saponins (2% on DM basis) in TMR–2 replaced wheat straw partially maintained the R: C ratio similar to TMR–1 (60:40). DM intake, nutrient utilization and enteric methane emission were studied on both feeding regimes. DM intake (kg/d) in buffalo calves was higher on TMR–2 than on TMR–1, similarly on uniform basis (kg/100 kg bw) it was also higher on feeding TMR–2. Nutrient digestibility and nitrogen intake on feeding TMR–2 was higher than that on feeding TMR–1, which resulted in higher nitrogen excretion through faeces and urine. Methane emission on feeding TMR–1 and TMR–2 was 18.11 and 12.45 g/kg DMI, respectively, showed a reduction of 32% due to the addition of 30% lucerne fodder (II cut) in TMR–2. Thus, the saponins supplied through lucerne fodder (total intake 29.58 g/d) decreased methane emission in buffalo calves. GE loss in the form of methane was more on feeding TMR–1 (5.73%) than that on TMR–2 (3.93%). The lower loss of GE in form of methane on feeding TMR–2 showed that incorporation of lucerne fodder to straw based ration can increase DMI, nutrient utilization in one hand and mitigate methane emission on another. As production of lucerne fodder is a common and a traditional practice in India, therefore, incorporation of lucerne fodder as a source of protein in total mixed ration seems more practical and promising for the mitigation of methane than the other strategies. Thus, there is urgent need to explore natural feeds and herbs having saponins and safe level of their incorporation in the ration.